Portable Echo / Khairul Irfan Khairul Nizam ... [et al.] - Khairul Nizam, Khairul Irfan; Borhan, Muhammad Haiqal Hazeeq; Mohd Ali, Alia Nazirah; Radzuan, Syafiqah Syahirah; Zulkafli, Akhmal Norhisham; Ahmad Subri, Nurul Najihah (2021)
The business model canvas is a great tool to help us to understand a business model in a straightforward, structured way. This canvas will lead to insights about the customers we are going to serve, what value propositions are offered through what channels, and how our company makes money. We can also use the business model canvas to understand the business model or that of a competitor. The Business Model Canvas was created by Alexander Osterwalder, of Strategyzer. The business model canvas is a shared language for describing, visualizing, assessing and changing business models. There are nine blockchain of BMC which are customer segments, value propositions, channels, customer relationship, revenue streams, key resources, key activities, key partner, and cost structure. Each of the business model canvas's nine blocks must be determined by the company. BMC describes the rationale of how an organization creates, delivers and captures value. With BMC, we will always have an overview of what our business model really is. It also shows which activities are not so important or even stand in the way of the goal. Because the BMC sharpens the view of the essentials, we can further improve our business model. The BMC is perfect as a base to let our thoughts run free. We can also test alternative models for the business idea and find new combination possibilities. BMC brings the business idea into a clear structured form. This has the advantage that others can quickly understand and discuss our business model. The BMC offers an overview of the business idea from every perspective. Thus, for example, controlling, the strategy department or management quickly receive exactly the information that is important to them.